2016
DOI: 10.1016/j.pmatsci.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Keratin: Structure, mechanical properties, occurrence in biological organisms, and efforts at bioinspiration

Abstract: a b s t r a c tA ubiquitous biological material, keratin represents a group of insoluble, usually high-sulfur content and filament-forming proteins, constituting the bulk of epidermal appendages such as hair, nails, claws, turtle scutes, horns, whale baleen, beaks, and feathers. These keratinous materials are formed by cells filled with keratin and are considered 'dead tissues'. Nevertheless, they are among the toughest biological materials, serving as a wide variety of interesting functions, e.g. scales to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
502
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(512 citation statements)
references
References 252 publications
(448 reference statements)
1
502
0
9
Order By: Relevance
“…In order to overcome these limitations, collagen or its denatured protein-that is, gelatin-have been used in the crosslinking form, 2 or in combination with biodegradable polymers including poly(lactic acid), 3,4 poly(glycolic acid) 5 and their copolymer poly(lactic-co-glycolic acid) (PLGA), 6 and poly(Δ-caprolactone) (PCL) 7,8 to improve the in vitro and in vivo biomechanical stability. 20,21 Recent works demonstrated that keratin-based materials may be easily designed in the form of films, 22 hydrogels, 23,24 sponges, 25 fibers, 26 without altering the natural pathway of amino acid sequences, similarly to those required to promote cell adhesion in ECM. For instance, silk-based materials have been largely considered for their capability to improve proliferation also supporting mechanical properties to the scaffold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome these limitations, collagen or its denatured protein-that is, gelatin-have been used in the crosslinking form, 2 or in combination with biodegradable polymers including poly(lactic acid), 3,4 poly(glycolic acid) 5 and their copolymer poly(lactic-co-glycolic acid) (PLGA), 6 and poly(Δ-caprolactone) (PCL) 7,8 to improve the in vitro and in vivo biomechanical stability. 20,21 Recent works demonstrated that keratin-based materials may be easily designed in the form of films, 22 hydrogels, 23,24 sponges, 25 fibers, 26 without altering the natural pathway of amino acid sequences, similarly to those required to promote cell adhesion in ECM. For instance, silk-based materials have been largely considered for their capability to improve proliferation also supporting mechanical properties to the scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In this context, alternative proteins have been more recently tested alone or in combination with other polymers to design protein-based fibrous scaffolds with peculiar functionalities for tissue engineering applications. 21,27 In particular, wool keratin is biocompatible, biodegradable, nonimmunogenic, does not induce inflammatory response and promotes wound healing by stimulating human keratinocytes migration. [11][12][13] Moreover, silk fibroin from Bombix mori has been frequently preferred to the collagen for the fabrication of fibrous scaffolds, 14,15 not being extracted from animals.…”
Section: Introductionmentioning
confidence: 99%
“…α keratin is the main constituent of hair, nail, and skin surface (stratum corneum) . Its structure is mainly in the form of α helix by hydrogen bonding among peptide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Wool is a keratinous material with specific structure, mechanical behaviour and physical-chemical properties (Wang et al, 2016). A clean wool fibre contains approximately 82% keratinous protein with high concentration of cysteine, approximately 17%, a protein material with a low cysteine content called "nonkeratinous material" mainly localized in the complex of the cell membrane and approximately 1% of the non-protein material is made up of waxy lipids, plus a small amount of polysaccharide material (Lewis and Rippon, 2013).…”
Section: Introductionmentioning
confidence: 99%